Efficacy of glial growth factor and nerve growth factor on the recovery of traumatic facial paralysis - Yildiz, Mucahit; Karlidag, Turgut; Yalcin, Sinasi; Ozogul, Candan; Keles, Erol; Alpay, Hayrettin Cengiz; Yanilmaz, Muhammed (Springer, 2011)
The aim of this study was to assess the effects of Glial growth factor (GGF) and nerve growth factor (NGF) on nerve regeneration in facial nerve anastomosis. In this study, approximately a 1-mm segment was resected from the facial nerve and the free ends were anastomosed. All animals underwent the same surgical procedure and 30 rabbits were grouped randomly in three groups. Control group, the group without any medications; NGF group, the group receiving 250 ng/0.1 ml NGF in the epineurium at the site of anastomosis; GBF group, the group receiving 500 ng/0.1 ml GGF in the epineurium at the site of anastomosis. Medications were given at the time of surgery, and at 24 and 48 h post-operatively. After 2 months, the sites of anastomosis were excised and examined using the electron microscope. It was found that the best regeneration was in the group receiving GGF as compared to the control group in terms of nerve regeneration. Schwann cell and glial cell proliferation were found to be significantly higher in the group receiving GGF as compared to the group receiving NGF. Besides, the number of myelin debris, an indicator of degeneration, was significantly lower in the group with GGF as compared to NGF and control groups (p < 0.005). Using GGF and NGF in order to increase regeneration after nerve anastomosis in experimental traumatic facial nerve paralysis may be a hopeful alternative treatment option in the future. However, further studies on human studies are required to support these results.
Keywords: Facial nerve anastomosis; Glial growth factor; Nerve growth factor